Projecting Future Chronic Coastal Hazard Impacts, Hotspots, and Uncertainty at Regional Scale - Meredith Leung; Laura Cagigal; Fernando Mendez; Peter Ruggiero (Earth's Future, 2024)
Abstract While there is high certainty that chronic coastal hazards like flooding and erosion are increasing due to climate change induced sea‐level rise, there is high uncertainty surrounding the timing, intensity, and location of future hazard impacts. Assessments that quantify these aspects of future hazards are critical for adaptation planning under a changing climate and can reveal new insights into the drivers of coastal hazards. In particular, probabilistic simulations of future hazard impacts can improve these assessments by explicitly quantifying uncertainty and by better simulating dependence structures between the complex multivariate drivers of hazards. In this study, a regional‐scale probabilistic assessment of climate change induced coastal hazards is conducted for the Cascadia region (Northern Washington to Northern California), USA during the 21st century. Three co‐produced hazard proxies for beach safety, erosion, and flooding are quantified to identify areas of high hazard impacts and determine hazard uncertainty under three sea‐level rise scenarios. A novel chronic coastal hazard hotspot indicator is introduced that identifies areas that may experience significant increases in hazard impacts compared to present day conditions. We find that beaches near the California‐Oregon border and in Northern Washington have larger hazard impacts and hazard uncertainty due to their morphologic setting. Erosional hazards, relative to beach safety and coastal flooding, will increase the most in Cascadia during the 21st century under all sea‐level rise scenarios. Finally, we find that hazard uncertainty associated with wave and water level variability exceeds the uncertainty associated with sea‐level rise for most of the 21st century.